ISOLASI DAN IDENTIFIKASI MOLEKULER BAKTERI PENGHASIL ENZIM PROTEASE PSEUDOMONAS STUTZERI ISTD4 DARI TEMPE GEMBUS PASCA FERMENTASI 1 HARI - Wa Ode Inayatul; Sakti Imam Muchlissin; Ana Hidayati Mukaromah; Sri Darmawati; Stalis Norma Ethica (Universitas Muhammadiyah Semarang, 2018)
Proteaseis a group of enzymes that play an important role in biochemical reactions, whichc a use protein break down. Protease is among main enzymes used in industry, which commercial value reach 60% of total enzymes world wide. This study a imed toisolat protease-producing bacterium found on tempe gembus in after 1-day post-fermentation and to identify the bacterial isolat obtained based on the analysis of its 16S rRNA gene. Isolati on and purification process wasd one using Nutrient Agar media with spread technique. The protease production test was carried out on skim milk agar medium. The molecular identification process was performed by analyzing sequence of 16S rRNA gene fragment of bacteria amplified using both forward primer F (F:5'- AGAGTTGATCCTGGCTCAG-3'), and reverse primer R (R:5'- GGTTACCTTGTTACGACTT-3') by Polymerase Chain Reaction (PCR) method. The amplified DNA from PCR was then sequenced. From the isolation process a bacterial strain that has a proteolytic activity based on observation of clear zone area with a diameter of 85 mm was obtained. From sequence alignment result using BLAST (Basic Local Alignment Search Tool) the fragment of 16S rRNA gene of strain ISTD1.4 obtained has similarity level of 98% with fragment of 16S ribosomal RNA gene of bacterium Pseudomonas stutzeri strain E141. In conclusion, strain ISTD1.4 is a potential protease-producing bacteria and is identified as Pseudomonas stutzeri ISTD4. Keywords: Bacterial isolation, molecular identification, proteolytic bacteria, 16S rRNA gene